Photoelastic analysis of stress generated by a silorane-based restoration system - Murilo Baena Lopes; Natália Valarini; Sandra Kiss Moura; Ricardo Danil Guiraldo; Alcides Gonini Júnior (Sociedade Brasileira de Pesquisa Odontológica, 2011)
Silorane-based composite, an epoxy material, was marketed as promising less polymerization contraction than conventional restorative materials. The aim of this study was to evaluate, by means of photoelasticity, the polymerization stress generated by a silorane-based composite. Thirty photoelastic rings with orifices measuring 5 mm (d) × 3 mm (h) were prepared and divided into 6 groups (n = 5) according to the material tested. The inside walls of the rings were sandblasted with aluminum oxide, after which the restorative materials were inserted into the orifices and photoactivated according to the manufacturer's instructions. The specimens were analyzed and the visual representation of the stress was measured considering the isochromatic ring of first order. The data were converted to MPa and subjected to ANOVA and Tukey's test (α= 0.05). The adhesive Filtek P-90 (G5) showed high contraction stress (p < 0.05) when compared to G1, G2, G3, G4, and G6, which did not differ from each other (p > 0.05). The composite Filtek P-90 showed similar contraction stress compared to the conventional composite and, additionally, its adhesive showed higher stress than did the etch-and-rinse 2-step adhesive.